Responsibility and the response : sustaining information systems in developing countries. - Agha, Syed Salim (1992)
Discusses the level of information use and the general state of information systems in developing countries. Urges development planners, information professionals and aid agencies to work individually and collectively to develop programmes to limit disparities in the development process, support 'needs-based' information programmes, services and activities.